Multiscale oil-stocks dynamics: the case of Visegrad group and Russia. Issue 1 (1st January 2020) - Živkov, Dejan; Đurašković, Jasmina; Papić-Blagojević, Nataša
Abstract: This paper tries to determine the strength of the interdependence between Brent oil market and the stock markets of oil importing Visegrad group countries and oil exporting Russia in different time-horizons. The paper uses several novel and elaborate methodologies – bivariate DCC-EGARCH model, wavelet correlations and phase difference. The results of DCC model show that all dynamic correlations between Brent oil and the selected stock indices are low at daily-frequency level. The magnitude of mutual correlations does not exceed 20% for Visegrad countries, while for Russia it goes little bit over 30%. Wavelet correlations in short-term confirms DCC results, whereby this relatively weak connection is found up to 32 days. However, in midterm and long-term, wavelet correlations strengthen, and go above 50% in midterm and even beyond 80% in long-term for majority of the indices. Slovakian SAX index has stronger wavelet correlation in 32 days than in 64 days, and it goes around 23%. This means that SAX can be coupled with Brent oil for diversification purposes in both short-term and midterm portfolios. Besides, phase-difference methodology provides an evidence that SAX was in anti-phase position in two separate occasions, meaning that SAX can also serve well for hedging purposes.